Fitrah: Becoming a Proportional Human (Comparative Study: Indonesian Tafsir Perspectives) - Vijay Asyfa Betay Seer; Muhammad Ali Fuadi; Sukron Azhari (ASTEEC, 2024)
Often human fitrah is interpreted as human potential in knowing good and bad, but if explored more deeply, human fitrah has a forming component. Tafsir alMisbah and alAzhar were chosen to unravel these components. Both of these interpretations have a uniqueness that is the use of adaby ijtima'i or societal style, but different angles of approach and orientation. Quraish Shihab tends to be systematic, structural, and psyco-sociological. Meanwhile, Hamka tends to be philosophical, Sufistic, and sociological. This research is qualitative research using literature review data. This research uses a comparative method. The research steps by explaining the concept of the study in general, then examined based on both interpretations referring to the object of the verse that can represent aspects of fitrah in detail. According to tafsir alMisbah, human nature is a facility from God for humans to recognise Him and obey Him. Meanwhile, according to the interpretation of al-Azhar, human nature is a means of acknowledging the existence of the Creator since humans can use reason. Dimensionally, human nature is divided into three parts, 1) fitrah jismiyyah, 2) fitrah nafsiyyah (i.) nafs, ii.) 'aql, iii.) qolb), 3) fitrah ruhiyyah. All three function differently but cannot operate partially, the combination of aspects collaborates to become fitrah.